An All‐Organic Elastomeric Electret Composite. Issue 1 (26th October 2016) - Ko, Yee Song; Nüesch, Frank A.; Damjanovic, Dragan; Opris, Dorina M.
Abstract : Copolymer nanoparticles with a highly polar repeating unit are blended in an elastic matrix and poled at elevated temperatures. The composite exhibits piezoelectricity due to the overall polarization imparted by the particles, which can be easily modulated thanks to the soft matrix.